IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA KONSENTRASI BELAJAR SISWA KELAS 3 DI SDN KEDAUNG 1 - Fitria Rosmi; Karima Tsania Husin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the problrm of low student concentration during civics learning, which tenden to be passive and lacked active student involment in the learing process. This study aimed to describe the implementation of the jigsaw cooperative learing model on student concentration in civics in third grade students at SDN Kedaung 1. This stude used a qualitative approach whith descriptive methods. The subjects were selected using a purposive sampling technique: a classroom teacher and three third grade students at SDN Kedaung 1. Data collection was conducted through observation, interviews, and documentation. Data analysis was carried out through the stages of data collection, data redaction, data presentation, and drawing conclusions. The results showed that the implementation of the jigsaw cooperative learning model was carried out through five stages: forming home groups and expert groups, dividing tasks and delivering material to home groups, expert group discussions, delivering material to home groups, presenting discussion results, and administering a quiz. Each stage in this model contributes to students’ learning concentration, including cognitive (understanding and remembering material), affective (interest and attention), psychomotor (directed physical activity), and language (communicating and listening skills). The jigsaw model fosters individual responsibility and teamwork, enabling students to be more focused, active, and enthusiastic in participating in learing. Therefore, it can be concluded that implementing the jigsaw cooperative learing model effectively improves students’ learning concentration in civis (PKN) and is highly relevant for elementary school to create a participatory and meaningful learning environment.